ISTILAH KEKERABATAN DALAM BAHASA INGGRIS DAN BAHASA KAYUPULO (SUATU ANALISIS KONTRASTIF) - Baransano, Astrid (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research is an attempt to describe and analyze the terms of address in the English and Kayupulo language. Both languages have two different groups of languages which have specific patterns of kinship terminologies. Both English and Kayupulo languages have a special and unique set of terms to indicate their kinship terminologies. The aim of this research is to compare and contrast the terms of address between English and Kayupulo language using Ladoâ€™s concept as well as using a descriptive method by Burling (1971) in which kinship terms are characterized by dimensions called â€œconsanguinealâ€™ and â€œafinalâ€ whereas the concepts relating to the terms of address use the methods of Wardaugh, Burling and Lounsburry quoted in Leech to find out the similarities and differences. The English data were collected from several relevant text books and some sources from internet and previous thesis about the term of address that has been done before, whereas the Kayupulo language data were collected from informants through investigation. The result of this research shows that English and Kayupulo language terms of address have similarities in terms of sex, generation, lineage and age. The differences are that the English terms of address do not separate the age of relatives while Kayupulo language does. In terms of generation, the English and Kayupulo have the same generation such as four generations above and below ego. Â  Key words: Term of address, Analysis Contrastive, Generation